2022
DOI: 10.5194/wcd-3-173-2022
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean cyclones: current knowledge and open questions on dynamics, prediction, climatology and impacts

Abstract: Abstract. A large number of intense cyclones occur every year in the Mediterranean basin, one of the climate change hotspots. Producing a broad range of severe socio-economic and environmental impacts in such a densely populated region, Mediterranean cyclones call for coordinated and interdisciplinary research efforts. This article aims at supporting these efforts by reviewing the status of knowledge in the broad field of Mediterranean cyclones. First, we focus on the climatology of Mediterranean cyclone track… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 263 publications
2
50
0
Order By: Relevance
“…Case studies revealed the crucial role of mountains for the formation of specific cyclones, as almost the entire PV was produced near them. Therefore, the resolution of diabatic processes near mountains is crucial for correctly predicting the intensity of cyclones, as previously highlighted by Flaounas et al (2022). Our climatological study confirmed that the lower-tropospheric PV anomaly can be produced to a large degree in the environment.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Case studies revealed the crucial role of mountains for the formation of specific cyclones, as almost the entire PV was produced near them. Therefore, the resolution of diabatic processes near mountains is crucial for correctly predicting the intensity of cyclones, as previously highlighted by Flaounas et al (2022). Our climatological study confirmed that the lower-tropospheric PV anomaly can be produced to a large degree in the environment.…”
Section: Discussionsupporting
confidence: 83%
“…The Mediterranean is one of the most cyclogenetic region in the world (Trigo et al, 1999;Ulbrich et al, 2009;Neu et al, 2013). Mediterranean cyclones are prominent high-impact weather systems that have been increasingly analyzed in the last years and thus, the driving processes of genesis and intensification of Mediterranean cyclones are fairly well known (Flaounas et al, 2022). They typically form in response to upper-tropospheric systems, such as potential vorticity (PV) cutoffs or narrow, meridionally-extended troughs that correspond to PV streamers (Appenzeller and Davies, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Three of these, called Qendresa (2014), Zorbas (2018), and Apollo (2021), strongly impacted the coast of south-eastern Sicily, in particular in Massolivieri, Maddalena Peninsula, and Varco 11 (Figure 2), with duration ranging from 4 to 7 days. As the Ionian Sea is not an area eligible for the formation of Tropical Cyclones, these phenomena occur due to a Tropical Transition (TT) process that can change an extratropical system into a tropical system or induce a hybrid cyclone [47,48]. However, several authors predict that, soon, climate changes could modify medicanes, decreasing the frequency of their occurrence but increasing the strength of their impacts [49].…”
Section: Geographic Frameworkmentioning
confidence: 99%
“…All of the above can increase the frequency and intensity of adverse cyclone-related hydrometeorological and hydrological events, for example torrential precipitation, wind surges, severe river floods, landslides [3]. Considering these risks, the Mediterranean Basin is particularly vulnerable to climate change [4].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, an increase in sea surface temperatures and latent heat fluxes increase convection, therefore thermodynamic processes become more important. On the other hand, higher temperature increase in the upper troposphere increases atmospheric stability [3,4]. In addition, a warmer atmosphere can hold more moisture according to the Clausius-Clapeyron equation [3], which is expected to lead to increased water vapor transport [5] and cyclone-related precipitation [6,7], for example over the Western Atlantic and Mediterranean region [8].…”
Section: Introductionmentioning
confidence: 99%